PENTINGNYA PENDIDIKAN SKI DALAM SHAPING KARAKTER SISWA DI ERA MODERN - alifia (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
Character education in Madrasah Ibtidaiyah plays a crucial role in shaping students in the modern era. One approach that can be taken is through skill-based learning, which enriches and develops the dimensions of students' characters. This research aims to explore the urgency of skill-based learning in shaping the character of students in Madrasah Ibtidaiyah in the modern era. This study employs qualitative analyses. Participants in the research include Madrasah Ibtidaiyah students as samples, with data collected through interviews, observations, and questionnaires. Data analysis is conducted by comparing the development of students' characters before and after the implementation of skill-based learning. The research findings indicate that skill-based learning has a positive impact on the development of students' characters. They not only acquire additional skills but also show improvement in aspects such as leadership, cooperation, and resilience. These findings illustrate that skill-based learning is significantly relevant in responding to the demands of the modern era. In the context of Madrasah Ibtidaiyah, the implementation of skill-based learning can be an effective strategy in preparing students to face the complexities of the modern world. Therefore, efforts to incorporate skill-based learning into the Madrasah Ibtidaiyah curriculum should be a priority, with a focus on sustainability and adaptability to the changing times. Kata Kunci: Skill-Based Learning, Student Character, Madrasah Ibtidaiyah, Modern Era, Islamic Education.